1984
DOI: 10.1038/311350a0
|View full text |Cite
|
Sign up to set email alerts
|

Apparent discontinuous transcription of Trypanosoma brucei variant surface antigen genes

Abstract: The repeated mini-exon sequence that encodes the first 35 base pairs of all variant surface antigen mRNAs of Trypanosoma brucei directs the synthesis of a discrete 137-nucleotide transcript. It thus seems that variant surface antigen mRNAs are transcribed discontinuously, and we present two alternative models for how this might occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
133
0
1

Year Published

1985
1985
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(139 citation statements)
references
References 42 publications
(8 reference statements)
5
133
0
1
Order By: Relevance
“…Most of the differences were 1 or 2 bp insertions or deletions, which particularly occured in non-transcribed homopolymer tracts. Similar levels of mismatch occur between 1.4 kb elements isolated from a given cloned cell line or between different T. brucei stocks (11,13,24,25).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Most of the differences were 1 or 2 bp insertions or deletions, which particularly occured in non-transcribed homopolymer tracts. Similar levels of mismatch occur between 1.4 kb elements isolated from a given cloned cell line or between different T. brucei stocks (11,13,24,25).…”
Section: Resultsmentioning
confidence: 74%
“…Orphons have since been found in gene families as diverse as the 5S and tRNA genes of Xenopus laevis (2), a major tandem repeat family from the human X chromosome (with dispersed members on autosomes) (3), and genes encoding the rRNAs of yeast (1). Both RNA and DNA mediated mechanisms of gene dispersal have been proposed to account for the (11)(12)(13). The vast majority of the 100 to 200 1.4 kb units are directly and tandemly repeated in the genome, but a few are orphons (6).…”
Section: Introductionmentioning
confidence: 99%
“…6A and B, lanes 3), indicating that the actin genes and the SL sequences are not closely linked in the genome. These combined results strongly suggest that trans splicing of the SL does occur in 0. volvulus, as proposed for the other organisms in which an SL has been detected (6,16,22,23,27,28).…”
Section: Ttgtagtcaaggttacgcgccaaaaaagagcgctctt---gcgctaaaaatagcgccttamentioning
confidence: 99%
“…The trypanosome SL is encoded in a repetitive DNA element of which there are about 200 copies in Trypanosoma brucei (8) and from which is transcribed an 85-to 140-nucleotide RNA species with the SL at its own 5' end. Current evidence suggests that the SL is transferred, in a trans-splicing event, from this small initial transcript to precursor RNAs of all proteincoding genes to yield mRNAs possessing the SL at their 5' ends (6,22,27). The raison d'etre of the trypanosome SL is not known, although it has been suggested that it participates in cleavage of polycistronic RNAs from tandem genes to generate monomer RNA units (17) and contributes a 5' CAP structure to those mRNAs (18).…”
mentioning
confidence: 99%
“…It is possible that the apo-protein is synthesized but then is rapidly degraded; however, the unique biology of T. brucei allows for possible mRNA modifications which could interfere with mRNA translation. Most, if not all, translatable mRNAs in trypanosomes contain a unique 5' miniexon (7,10,25). This 39-mer, which is trans-spliced onto mRNAs, may be involved in the recognition of translatable mRNAs.…”
Section: Resultsmentioning
confidence: 99%